Letter from Edward N. Kent to James Curtis Booth, April 13, 1853 - Kent, Edward (1853)
Edward N. Kent writes to James Curtis Booth (1810-1888) fretting that the position he applied to at the United States Assay Office may be filled politically.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City; Assaying